Conceptual theoretical tools for analysis of decision making in public economics committees (2014)
This article is a theoretical work on the topic of decision making in public economics committees. It will present a First some basics about decisions such as: 1 conditions - 2 individual factors 3 - group and 4 - classifications of particular decisions related to the field of public policy. Later in January - will be presented some models of decision making related to aspects of economic theory and 2 - empirical work on decision making in committees specifically in public economics committees both fiscal and monetary, which can serve as a framework for reference for future research.